Using macroeconomic computable general equilibrium models for assessing poverty impact of structural adjustment policies - Haider A. Khan (Asian Development Bank Institute (ADBI), 2004)
The paper surveys selectively and analytically the implications of the various (macroeconomic) computable general equilibrium (CGE) models constructed for the purpose of integrating poverty analysis with the usual macroeconomic variables and relationships. It is found that a dual-dual production structure with sufficient details on the labor markets and household side can capture some of the effects of trade liberalization on poverty reduction. Further work needs to be done in expanding the export sectors and adding financial structure in order to carry out a detailed analysis of the impact of both trade and financial liberalization on poverty reduction. To this end a preliminary model is presented which can be compactified to carry out this type of analysis. Four broad categories of Asian economies are suggested for further analysis. As a first step in this direction, a modified model based on data about the structure of Bangladesh economy can be used as a 'generic' model for the least developed poor Asian economies.
Keywords: 330; Wirtschaftliche Anpassung; Armut; Armutspolitik; Makroökonomischer Einfluss; CGE-Modelling